Effectiveness assessment of the management reporting system implementation (Economics and region, 2024)
The study provides a comprehensive justification for the necessity and advantages of a systematized management reporting system in facilitating crucial strategic and tactical decision-making processes. The article delves into the primary stages of implementing a management reporting system, including the preparatory phase, system design, development, testing, and subsequent implementation, followed by continuous operation and refinement. This study is conducted within the framework of a management accounting automation system, leveraging advanced software products in the realms of accounting and enterprise management. Particular emphasis is placed on incorporating modern technologies, such as artificial intelligence, cloud computing, and Big Data, which play a pivotal role in enhancing management decisions' efficiency, precision, and timeliness. The author has meticulously developed a step-by-step algorithm for the implementation of a management reporting system, ensuring that each stage is aligned with the overarching objectives of the enterprise. To evaluate the effectiveness of the management reporting system, the author proposes the use of key performance indicators (KPIs). These KPIs serve as the fundamental metrics for assessing the success of the system's implementation, encompassing aspects such as accuracy, timeliness, completeness, quality of information, cost-effectiveness, user satisfaction, risk analysis, and system reliability. The analysis of the data reveals that integrating these cutting-edge technologies significantly enhances the quality of management information, reduces data processing costs, and boosts the productivity of accounting and analytical teams. The study's findings confirm that adopting modern technologies within the management reporting system not only facilitates the attainment of the enterprise’s strategic goals but also bolsters its competitiveness and adaptability in the face of rapid changes in the business environment. In conclusion, the study provides detailed recommendations aimed at refining the process of implementing and continuously optimizing the management reporting system, thereby ensuring its peak efficiency and alignment with the evolving needs of the business.
Keywords: reporting; information; accounting; decision-making; management